Índice de possibilidade de conversão à agricultura (ipca): uma ferramenta na elucidação do fenômeno da expansão da fronteira agrícola em Goiás - Lopes, Marcos Vinícius (2016)
The world population recently surpassed the amount of 7 billion people. The Food and Agriculture Organization, FAO, reported that there is more than 1 billion people on the map of global hunger. Increase food production, reduce poverty and hunger, combined with local, regional and global environmental problems, it has been the major challenges for global managers. It is in this context that the present tropical savannas as potential producers and providers, specially of food to meet these demands for proteins, grains, fiber and energy for the entire globe. The Cerrado, second Brazilian biome in area, is the Brazilian savannah, which holds a large and rich biodiversity. Over the last fifty years, the process of land use and cover changes brought about profound changes in the Cerrado, especially in the vast, flat areas of the State of Goiás. Group study and research of the phenomenon of land-use land cover change and they are developing research in various regions and continents of the world with the use of mathematical / statistical modeling and logistic regressions in urban and rural areas. Model such phenomena helps to outline scenarios for the optimization of food production, safeguarding the natural areas remaining. This paper presents the development of research and creation of the possibility of conversion to the Agriculture Index (IPCA). This index, based on logistic regression, seeks to establish patterns in the occurrence of the expansion of the agricultural frontier in the Cerrado Goiano. The results of this research demonstrate that allowed the construction of models to assess use change processes and land cover is fully feasible. Although it was not possible the ranking of variables, drivers in degree of importance, it was possible to establish the top 25 attributes in the agricultural expansion process in the cut of the study. The IPCA has measured that maintaining the current agricultural expansion characteristics in the last 12 years, there are more than 58,790 km2 (~ 17.3% of the territory of Goiás) able to be converted to the practice of agriculture. This increase would represent more than double the area devoted to agricultural use in the State of Goias under the criteria of IPCA. This construction requires the knowledge in several areas, since it requires a transdisciplinary approach to the problem to understand its complexity, in order to identify the variables, drivers who run and provide the alteration processes of land use, to enable the instrument to assist and support managers,public and private, in decision-making with regard to this important Brazilian biome.